Investigation of the absorption of CO2 in ionic liquid (Bangladesh Journal of Scientific Research, 2016)
Due to environmental concerns, current interest is the development of technologies that may be able to remove CO2 efficiently from exhaust gases and thus avoid its dispersion in the atmosphere. The density functional theory (DFT) calculations with the modern continuum solvation model (IEFPCM-SMD) was used to study the mechanism of CO2 absorption in room temperature ionic liquid such as, [EMIM][BF4] (1-ethyl-3- methylimidazolium tetrafluoroborate). We determine the minimum energy structures and to determine the possible binding sites for CO2 absorption process in [EMIM][BF4]; by comparing the relative minimum energy of [EMIM][BF4] in the presence and absence of CO2.Bangladesh J. Sci. Res. 29(1): 41-46, June-2016